The co-evolution of innovation networks: Collaboration between West and East Germany from 1972 to 2014 - Bogang Jun; Seung-Kyu Yi; Tobias Buchmann; Matthias Mueller (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2016)
This paper describes the co-evolution of East and West German innovation networks after the German reunification in 1990 by analyzing publication data from 1972 to 2014. This study uses the following four benchmark models to interpret and classify German innovation networks: the random graph model, the small-world model, the Barabási-Albert model, and the evolutionary model. By comparing the network characteristics of empirical networks with the characteristics of these four benchmark models, we can increase our understanding of the particularities of German innovation networks, such as development over time as well as structural changes (i.e., new nodes or increasing/decreasing network density). We first confirm that a structural change in East-West networks occurred in the early 2000s in terms of the number of link between the two. Second, we show that regions with few collaborators dominated the properties of German innovation networks. Lastly, the change in network cliquishness, which reflects the tendency to build cohesive subgroups, and path length, which is a strong indicator of the speed of knowledge transfer in a network, compared with the four benchmark models show that East and West German regions tended to connect to new regions located in their surroundings, instead of entering distant regions. Our findings support the German federal government's continuous efforts to build networks between East and West German regions.
urn:nbn:de:bsz:100-opus-12366
Keywords: 330; Innovation networks; Network dynamics; German reunification